We Were Never Environmentalists - Nathália Kneipp Sena (Fronteiras: Journal of Social, Technological and Environmental Science, 2015)
This essay was presented at the University of Brasilia as a final assignment required in the course “Special Topics in Social History – Frontier, Natural Resources and Environmental Conservation”. Students were supposed to elaborate an article with a critic view considering the ideas presented in the books and papers discussed in class. Therefore, the content of this work outlines several differences in the construction of the concept of frontier as time goes by and raises the question whether human beings were, have been or will ever be environmentalists. Keywords: Frontier; Environmentalism; Conservation of Natural Resources; Environmental Protection.